Development of an integrated method for implementation of food diets to medical and health institutions - Biletska, Yana; Badyhina, Hanna; Semeniuk, Alina (Technology audit and production reserves, 2020)
The object of research is the consumer preferences of visitors, the requirements of specialists in the field of science, production and catering. Existing diets, according to which visitors eat in sanatoriums and dispensaries, require immediate correction. A promising way is the development of specialized food culinary dishes and rations from them, which are successfully integrated and used, based on the mutual experience of specialists in the field of science, manufacturing enterprises and catering. This approach to solving the problem is the most effective and economically feasible, as evidenced by the accumulated experience and achievements of modern nutritional science. In the course of the study, the synectic method is used, based on the work of specialists in the field of science, production and catering. 4 working groups of 10–15 people each are formed. Scientists are employees of Kharkiv State University of Food Technology and Trade, V.N. Karazin Kharkiv National University, Lviv Polytechnic National University and V. Chornovol Sustainable Development Institute in Lviv (Ukraine). Food organizers: director, chief physician, nutritionist, chef of the Borisfen sanatorium (city of Berdsansk, Ukraine); chief doctor, nutritionist, head of the canteen of the Institute of Neurosurgery named after academician A.P. Romodanov of the National Academy of Medical Sciences of Ukraine (Kyiv, Ukraine); heads of the public organization «Lviv Regional Organization of the All-Ukrainian Ecological League» (Lviv, Ukraine); consumers – visitors to health facilities using the services 1–2 times a year. Within the framework of the study, an integrated implementation method is proposed, which will contribute to increasing the efficiency of using scientific developments. This will create a mechanism for the interaction of scientists with production and participants in the catering process with the end user. Due to this, solutions to the problem of national importance will be provided, which is associated with unbalanced diets.